2022
DOI: 10.3390/pharmaceutics14091967
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of Alpinia galanga Constituents and Investigation of Their Membrane Permeability by ChemGPS-NP and the Parallel Artificial Membrane Permeability Assay

Abstract: Alpinia galanga Willd., greater galangal, has been used for thousands of years as a spice as well as in traditional medicine. Its central nervous system (CNS) stimulant activity and neuroprotective effects have been proved both in animal models and human trials. However, the compounds responsible for these effects have not been identified yet. Therefore, the main constituents (p-OH-benzaldehyde (1), trans-p-coumaryl-alcohol (2), p-coumaryl-aldehyde (4), galanganol A (5), galanganol B (6), trans-p-acetoxycinnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The PAMPA experiment is widely used as an in vitro model for evaluating membrane permeability and transcellular permeation [ 26 , 27 , 28 , 29 , 30 ]. As shown in Figure 5 , compared with the free RAPA solution, the RAPA-NM exhibited a strong permeability potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAMPA experiment is widely used as an in vitro model for evaluating membrane permeability and transcellular permeation [ 26 , 27 , 28 , 29 , 30 ]. As shown in Figure 5 , compared with the free RAPA solution, the RAPA-NM exhibited a strong permeability potential.…”
Section: Resultsmentioning
confidence: 99%
“…This membrane permeation has also indicated the potential of improved in vivo corneal permeation [ 26 , 27 ]. The PAMPA experiment was performed as previously reported [ 28 , 29 , 30 ]. Briefly, free RAPA was dissolved in DMSO and further diluted with an artificial tears solution to obtain a RAPA concentration of 5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…It has its uses in cooking, traditional medicine, and cosmetics. Two varieties are most commonly described in the medical literature: Alpinia galanga and Alpinia officinarum [174][175][176][177]. Galangal is rich in phenolic compounds (acids and flavonoids), of which galangin is predominant.…”
Section: Galangalmentioning
confidence: 99%
“…No reliable studies on the bioavailability of galangin have been identified. It is suggested that further experiments are needed, and studies are being conducted to obtain extracts that are well absorbed from the gastrointestinal tract [176]. The use of galangin in clinical settings may be hampered by its characteristic chemical properties (as a 3hydroxyflavone, it has low solubility in water) [31].…”
Section: Galangalmentioning
confidence: 99%
“…As neuroprotective effects of A. galanga have been reported in several studies, the aqueous stability and gastro-intestinal/ blood-brain barrier (GI/BBB) permeability of the main compounds in the extract were investigated. 31 The phenolics (340, 342, 346, 351, 352, and 355) showed good permeability, which contributes to the neuroprotective effects of A. galanga. Four compounds with neuroprotective activity in A. oxyphylla were tested for BBB permeability, 2 and the order of permeability was 341, 147, 279, and 280.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%